2021
DOI: 10.3389/fpls.2021.631810
|View full text |Cite
|
Sign up to set email alerts
|

Plant Defense Responses to Biotic Stress and Its Interplay With Fluctuating Dark/Light Conditions

Abstract: Plants are subjected to a plethora of environmental cues that cause extreme losses to crop productivity. Due to fluctuating environmental conditions, plants encounter difficulties in attaining full genetic potential for growth and reproduction. One such environmental condition is the recurrent attack on plants by herbivores and microbial pathogens. To surmount such attacks, plants have developed a complex array of defense mechanisms. The defense mechanism can be either preformed, where toxic secondary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(78 citation statements)
references
References 357 publications
0
76
0
2
Order By: Relevance
“…However, a peak of jasmonic acid (JA), a hormone that is required in plant defence against necrotrophic fungi such as A. brassicicola, is observed in the middle of a light period in Arabidopsis [38]. Lack of a dark period may enhance plant resistance against A. brassicicola and also through extensive production of metabolites with antifungal properties, e.g., phenolic compounds or, characteristic for Brassicas, glucosinolates [39,40]. Glucosinolate biosynthesis is also regulated by light and it has been demonstrated that dark exposure decreases its content in Chinese cabbage seedlings [40,41].…”
Section: Differential Influence Of Day Length On Leaf Morphology and Necrosis Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a peak of jasmonic acid (JA), a hormone that is required in plant defence against necrotrophic fungi such as A. brassicicola, is observed in the middle of a light period in Arabidopsis [38]. Lack of a dark period may enhance plant resistance against A. brassicicola and also through extensive production of metabolites with antifungal properties, e.g., phenolic compounds or, characteristic for Brassicas, glucosinolates [39,40]. Glucosinolate biosynthesis is also regulated by light and it has been demonstrated that dark exposure decreases its content in Chinese cabbage seedlings [40,41].…”
Section: Differential Influence Of Day Length On Leaf Morphology and Necrosis Formationmentioning
confidence: 99%
“…Lack of a dark period may enhance plant resistance against A. brassicicola and also through extensive production of metabolites with antifungal properties, e.g., phenolic compounds or, characteristic for Brassicas, glucosinolates [39,40]. Glucosinolate biosynthesis is also regulated by light and it has been demonstrated that dark exposure decreases its content in Chinese cabbage seedlings [40,41]. Moreover, several phytopathogenic fungi, e.g., the necrotroph Botrytis cinerea, display a circadian rhythm, and light influences their development and stress responses [42,43].…”
Section: Differential Influence Of Day Length On Leaf Morphology and Necrosis Formationmentioning
confidence: 99%
“…The seeds of both genotypes were planted in plastic cones (25 × 5 cm) in a greenhouse and transferred to a climate-controlled growth chamber at the two-leaf stage at Agricultural Research Center-Hays, Kansas State University. The climate-controlled growth chamber was set to 23 ± 1 • C and a 14:10 h (light:dark) daylength, conditions known to facilitate both plant growth and SCA survival and reproduction [20] and plant defense mechanisms [67]. Seedlings of both the R and S genotypes were each infested at the three-leaf stage with fivefourth instar SCA nymphs.…”
Section: Aphid Infestation and Samplingmentioning
confidence: 99%
“…High temperature also damages the roots of plant cells by altering the cellular and molecular mechanisms. Visible symptoms appear on the roots as well as the damage leaves that ultimately suppress the seedling [9,10]. Elevated temperatures can reduce the germination potential of the seeds and, thus, results in poor germination and stand establishment.…”
Section: Effect Of Heat Stress On Cropsmentioning
confidence: 99%